Defining urban green infrastructure role in analysis of climate resiliency in cities based on landscape ecology theories - Shirgir, Elmira; Kheyroddin, Reza; Behzadfar, Mostafa (TeMA - Journal of Land Use, Mobility and Environment, 2019)
Cities are exposed to the risk of climate change and as a result, are very vulnerable. In recent years, to face the challenges caused by the climate change, the notion of climate resilience and specifically, urban ecological resilience, has been studied. Climate resilience is in focus of this paper and a subcategory of urban ecological resilience, which is defined as the urban resilience to the climate change. Also, urban green infrastructure has an established role as one of the strategies for adapting to climate change and for developing and promoting climate resilience in cities. Given the theoretical gap existing in this field, this question arises: "How and based on which features of the green infrastructure can we assess and analyze the climate resilience in a city?” To answer this question, the landscape ecology principles and relationship between these principles and the green infrastructure in the cities were used. The relationship was developed in the Yousef Abad neighborhood of Tehran and was qualitatively tested using the aerial images, field surveys and preparation of basic and analytical GIS maps. Finally, the "effective factors in assessing the climate resilience in cities using the urban green infrastructures based on landscape ecology" were obtained.